Iconografia teatral/performática amazônida - ROCHA, Raphael Andrade (Programa de Pós-Graduação em Artes - PPGArtes/UFPA, 2023)
MARTINS, B. A.; ALMEIDA, I. M. X. A. Universidade Federal do Pará, Instituto de Ciências da Arte (ICA)